Livros Escolares de Aritmética que circularam na Província de São Pedro do Rio Grande do Sul (1822-1889) - Schramm, Daiane de Almeida (2024)
The study presents research carried out in the field of History of Mathematics Education based on themes related to the circulation of school printed matter in the Brazilian Imperial period. Thus, its general objective is to analyze the circulation process of Arithmetic school books in the Province of São Pedro do Rio Grande do Sul during the imperial period (1822-1889). In the state of knowledge, research (theses, dissertations and articles) related to the issues surrounding this investigation was sought. In the end, 24 schoolbooks were identified from this project, by 19 authors, published mainly in the Province, predominantly in the cities of Porto Alegre and Pelotas. These works were located on websites such as Hemeroteca Digital, advertisements in periodicals of the time, news from publishing houses in the Region, as well as a search in physical libraries such as the Pelotas Public Library, Rio Grande Public Library, CEDOC- Centro de Studies and Investigations in History of Education, Public Archive of the State of Rio Grande do Sul, Public Library of Rio Grande do Sul. As for the authors, they were figures of renowned knowledge, most of them teachers of “individual classes” or instructional schools public or private. In general, they produced books, primers, compendia or manuals that served, initially, as a base text for teaching arithmetic to their students or other teachers. The printing presses, in which newspapers were printed, were the same ones responsible for producing these books. The circulation was small, and the books were sold in warehouses and apothecaries, along with other merchandise. Slowly, with the organization of education, whether on the initiative of the Empire or on a private initiative, there was an increase in the variety and circulation of schoolbooks. In total, 11 establishments were identified, including printers and publishers that produced and sold the identified works. Of these, nine were located in the Province, one in Portugal and one in Rio de Janeiro. Another aspect worth mentioning is the fact that the books produced during this period underwent a change in objective, from initially focusing on the teacher, they began to be prepared with the student as the objective, as they began to include exercises that had focus on learning. In accordance with our main theoretical reference Alain Choppin, we conclude that the schoolbook is a cultural product derived from advances in production techniques, changes in the publishing universe, economic scenarios, political and legislative nature. In this scenario, it is believed that schoolbooks began to be valued and popularized in the periods subsequent to the analysis undertaken here.